Influence of the constructive parameters of heat-accumulating electric converter on its energy characteristics - Левченко, Сергей Андреевич (Technology audit and production reserves, 2016)
The heat-accumulating electric energy converter based on direct heating of heat-accumulating substance through which electric current runs is offered for autonomous sources of heat water-supply. Three phase construction of heat-accumulating electric energy converter is considered. The mathematic model of converter and computer program of electric power and temperature in each elementary tank’s volume has been worked out. The dependences between geometrical sizes and converter’s electro-thermal characteristics are received. The technique of determining the optimal constructive parameters of the main heat-accumulating electric converter for solar heating systems using the proposed mathematical model is considered. Optimal constructive correlations of converter are received. Natural experiments to determine electro-thermal characteristics of converter have been conducted. The test results of research have been conducted. Economic effect of convertor’s using in solar heat-supply systems is expected by reducing natural gas consumption for heat water supply.